Epibacterial community patterns on marine macroalgae are host-specific but temporally variable - Lachnit, Tim; Meske, Diana; Wahl, Martin; Harder, Tilmann; Schmitz, Ruth (Environmental microbiology, 2011)
Marine macroalgae are constantly exposed to epibacterial colonizers. The epiphytic bacterial patterns and their temporal and spatial variability on host algae are poorly understood. To investigate the interaction between marine macroalgae and epiphytic bacteria, this study tested if the composition of epibacterial communities on different macroalgae was specific and persisted under varying biotic and abiotic environmental conditions over a 2-year observation time frame. Epibacterial communities on the co-occurring macroalgae Fucus vesiculosus, Gracilaria vermiculophylla and Ulva intestinalis were repeatedly sampled in summer and winter of 2007 and 2008. The epibacterial community composition was analysed by denaturing gradient gel electrophoresis (DGGE) and 16S rRNA gene libraries. Epibacterial community profiles did not only differ significantly at each sampling interval among algal species, but also showed consistent seasonal differences on each algal species at a bacterial phylum level. These compositional patterns re-occurred at the same season of two consecutive years. Within replicates of the same algal species, the composition of bacterial phyla was subject to shifts at the bacterial species level, both within the same season but at different years and between different seasons. However, 7-16% of sequences were identified as species specific to the host alga. These findings demonstrate that marine macroalgae harbour species-specific and temporally adapted epiphytic bacterial biofilms on their surfaces. Since several algal host-specific bacteria were highly similar to other bacteria known to either avoid subsequent colonization by eukaryotic larvae or to exhibit potent antibacterial activities, algal host-specific bacterial associations are expected to play an important role for marine macroalgae.